Analisis Pengolahan Keuangan pada UMKM Usaha Laundry Mawar di Daerah Salakan Sraten - Abbraham Sidiq; Dianing Widya Kusumastuti (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the financial management practices of the Mawar Laundry MSMEs in Salakan Sraten as a representation of the condition of micro businesses in rural areas that still apply conventional financial management systems. Financial management has a strategic role in maintaining business stability, efficiency, and sustainability, especially for MSMEs that face limited human resources, access to capital, and accounting literacy. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation of transactions and business assets. Data analysis is carried out inducively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that Laundry Mawar has not implemented a structured financial recording system, with personal and business finances still mixed and daily transactions that are not documented in writing. The main causative factors include low accounting literacy, time constraints, traditional habits, and lack of external assistance. The study recommends the implementation of a simple cash recording system, account segregation, asset recording based on economic age, and periodic financial literacy training. These findings make a theoretical and practical contribution to the literature on MSME financial management in rural areas, emphasizing the importance of simple accounting as the foundation for the sustainability and competitiveness of micro enterprises.